(untitled) (Research, Society and Development, 2021)
He interest in donkey milk has been highlighted due to studies related to its beneficial characteristics, it has similarities in palatability and composition when compared to breast milk. Milk of this species has been shown to be low in protein and fat, and rich in lactose, in addition to having antimicrobial properties, making it an ideal food for human supplement and mainly as an alternative food for children with allergy to cow’s milk protein. Therefore, the objective of this work was to study the lyophilization kinetics for donkey milk submitted to different freezing temperatures (-20, -60, -100 and -140ºC), as well as to determine the effective diffusivity and thermodynamic properties. The experimental data were subjected to analysis of the theoretical, semi-theoretical, semi-empirical and empirical drying models, and the parameters R2, Ra2, P (%), SE and DQM were determined. Among the drying models studied, the modified Cavalcanti-Mata model was the one that presented the best adjustment to the experimental data. In the models of Fick modified, Cavalcanti-Mata modified, Lewis modified and Page modified, the effective diffusivity decreased with the decrease of the freezing temperature and as a result of this, it appears that enthalpy and entropy decreased as the freezing temperature dropped and Gibbs’ free energy demonstrated that the process is not spontaneous.